Perbedaan Hasil Belajar Matematika Siswa Antara Model Contextual Teaching and Learning (CTL) dengan Realistic Mathematic Education (RME) - Wanelly, Widya; Yunisrul, Yunisrul; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research to knowing the differences in cognitive learning outcomes student of Mathematics Between Model Contextual Teaching And Learning (CTL) with model Realistic Mathematic Education (RME). This type of research is a quasi experiment research with non equivalent control group design. The sample in this research is class VA and VB SD 38 Lubuk Sao. Teknik data collection using test. Test the hypothesis in this study using the formula t-test. Based on the results showed that the average of the CTL class was 83,63  and the RME class average was 77,125. Based on the calculation of t test (t-test) on posttest obtained tcount (5,12) >  ttabel (1,69). As Ha is accepted, is mean differences in cognitive learning outcomes student of Mathematics Between Model Contextual Teaching And Learning (CTL) with model Realistic Mathematic Education (RME).